Material suppliers’ perspective on collaboration in industrial construction projects - Choi, Seogjae; O’Brien, William J. (Frontiers in Built Environment, 2025)
Material suppliers’ involvement in construction project planning has been recommended as an effective measure to improve project performance by using their expertise. However, the recommendation is not universal, and some researchers disputed the value of early involvement of suppliers depending on material type. Moreover, prior studies considered main contractors’ and owners’ perspectives mostly in examining how to increase the involvement of suppliers. To add material suppliers’ perspective, this study conducted interviews with experienced professionals from 16 material suppliers including standardized, make-to-order, and custom products. The results are specified by separating the type of materials and sub-phases of planning. The results show that custom product suppliers need to be involved in the feasibility and concept phases, make-to-order product suppliers need to be involved in the concept and detailed scope phases, and standardized product suppliers need to be involved in the detailed scope phase. The excerpts from the interview are provided for detailed benefits from the involvement at a desired time and the issues stemmed from later involvement than desired. From the material supplier perspective, this study establishes the value of material supplier involvement in the planning phase regardless of material type. These findings challenge established viewpoints supporting the later involvement of standardized material suppliers and describe the value such suppliers can add to industrial projects in the planning phase.